Partial characterization of venom from the colombian spider Phoneutria Boliviensis (Aranae:Ctenidae) (2015)
We report on the first studies on the characterization of venom from Phoneutria boliviensis (Aranae:Ctenidae) (F. O. Pickard-Cambridge, 1897), done with Colombian species.